Methylene blue administration in the compound 48/80-induced anaphylactic shock: hemodynamic study in pigs - Menardi,Antonio Carlos (2011)
PURPOSE: To verify if the methylene blue (MB) administration prevents and/or reverses the compound 48/80 (C48/80)-induced anaphylactic shock in pigs. METHODS: Female Dalland pigs were anesthetized and had the hemodynamic parameters recorded during the necessary time to administer some drugs and observe their effect. The animals were randomly assigned to one of the five groups: 1) control; 2) MB: the animals received a bolus injection of MB (2 mg/kg) followed by continuous infusion of MB (2.66 mg/Kg/h delivered by syringe infusion pump); 3) C48/80: the animals received a bolus injection of C48/80 (4 mg/kg); 4) C48/80+MB: the animals received a bolus injection of C48/80 (4 mg/kg) and 10 minutes after the C48/80 administration the animals received a bolus injection of MB (2 mg/kg) followed by continuous infusion of MB (2.66 mg/Kg/h delivered by syringe infusion pump); 5) MB+C48/80: the animals received a bolus injection of MB (2 mg/kg) and 3 minutes later they received a bolus injection of C48/80 (4 mg/kg). RESULTS: The intravenous infusion of MB alone caused no changes in the mean arterial pressure (MAP) showing that the administered MB dose was safe in this experimental model. The C48/80 was effective in producing experimental anaphylactic shock since it was observed a decrease in both MAP and cardiac output (CO) after its administration. The MB did not prevent or reverse the C48/80-induced anaphylactic shock in this model. In fact, the MAP of the animals with anaphylactic shock treated with MB decreased even more than the MAP of the animals from the C48/80 group. On the other hand, the C48/80-induced epidermal alterations disappeared after the MB infusion. CONCLUSION: Despite our data, the clinical manifestations improvement brings some optimism and does not allow excluding the MB as a possible therapeutic option in the anaphylactic shock.